Opting out? : why women really quit careers and head home - Stone, Pamela, 1950- (Berkeley : University of California Press, 2007)
Noting a phenomenon that might seem to recall a previous era, The New York Times Magazine recently portrayed women who leave their careers in order to become full-time mothers as "opting out." But, are high-achieving professional women really choosing to abandon their careers in order to return home? This provocative study is the first to tackle this issue from the perspective of the women themselves. Based on a series of candid, in-depth interviews with women who returned home after working as doctors, lawyers, bankers, scientists, and other professions, Pamela Stone explores the role that th
The dream team -- Family matters -- Home alone -- Gilded cages -- The choice gap -- Half-full, half-empty -- Mothers of re-invention -- Cocooning: the drift to domesticity -- Dreams and visions: getting there -- Appendix. Study methodology.
Includes bibliographical references (pages 277-285) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Stay-at-home mothers; Work and family; Choice (Psychology); Life change events; Choice Behavior; Life Change Events; Mères au foyer; Travail et familles; Choix (Psychologie); Événements stressants de la vie; FAMILY & RELATIONSHIPS -- Parenting -- Motherhood; SOCIAL SCIENCE -- Sociology -- General; Choice (Psychology); Life change events; Stay-at-home mothers; Work and family